Diseño del sistema de iluminación de algunas zonas comunes de la universidad Antonio Nariño sede sur mediante software Dialux en cumplimiento el reglamento técnico de iluminación y alumbrado público (Retilap) (2020)
energy efficiency is based on reducing the amount of energy consumed by electrical appliances this generates savings in the electricity bill and what is even more important we take care of the planet. In this project we designed the lighting for the parking areas, the cafeteria hall and the Antonio Nariño square, in compliance with the technical regulations for lighting and street lighting (RETILAP), recognizing the reasonable use of energy in order to contribute to sustainable development